The effect of C5 substitution on the photochemistry of uracil - Nachtigallová, Dana (2010)
A combined experimental and theoretical study on the excited-state behavior of the uracil analogues, 5-OH-Ura and 5-NH2-Ura is reported. Two-photon ionization and IR/UV double-resonant spectra show that there is only one tautomer present for each with an excited state lifetime of 1.8 ns for 5-OH-Ura and 12.0 ns for 5-NH2-Ura as determined from pump-probe experiments. The nature of the excited states of both species is investigated by means of multi-reference ab initio methods. Vertical excitation energies, excited state minima, minima on the crossing seam and reaction paths towards them are determined. Sizeable barriers on these paths are found that provide an explanation for the lifetimes of several nanoseconds observed in the experiment.